Extraintestinal manifestations at baseline, and the effect of tofacitinib, in patients with moderate to severe ulcerative colitis. (May 2021) - Rubin, David T.; Reinisch, Walter; Greuter, Thomas; Kotze, Paulo G.; Pinheiro, Marcia; Mundayat, Rajiv; Maller, Eric; Fellmann, Marc; Lawendy, Nervin; Modesto, Irene; Vavricka, Stephan R.; Lichtenstein, Gary R.
Introduction: Extraintestinal manifestations (EIMs) in patients with ulcerative colitis (UC) are common. Tofacitinib is an oral, small molecule Janus kinase inhibitor for the treatment of UC. We evaluated the efficacy of tofacitinib in patients with EIMs, and the impact of tofacitinib on EIMs in patients with UC in the OCTAVE clinical program. Methods: Data from two 8-week induction studies (OCTAVE Induction 1 and 2) and a 52-week maintenance study (OCTAVE Sustain) were analyzed. The effect of tofacitinib on efficacy outcomes stratified by EIM status, proportion of predefined prior and active EIMs at baseline, and change from baseline in EIMs were determined at the end of the treatment period (weeks 8 or 52), or at early termination. Results: At baseline of OCTAVE Induction 1 and 2, and OCTAVE Sustain, 27.0% and 9.0% of patients had a history of EIMs (prior or active), respectively. Patients treated with tofacitinib 10 mg twice daily (BID) achieved remission and had endoscopic improvement in all studies, irrespective of any history of EIMs. A greater proportion of patients had active peripheral arthritis at baseline of OCTAVE Induction 1 and 2 versus OCTAVE Sustain. In OCTAVE Induction 1 and 2, similar proportions of tofacitinib and placebo-treated patients with active peripheral arthritis experienced either no change (81.3% and 85.7%, respectively) or an improvement (15.6% and 14.3%, respectively). By week 52 of OCTAVE Sustain, improvements in active peripheral arthritis were only observed in tofacitinib-treated patients (16.7% and 33.3% with tofacitinib 5 and 10 mg BID, respectively). Conclusion: Any history of EIMs did not influence the efficacy of tofacitinib 10 mg BID for induction or maintenance of UC. The most common active EIM was peripheral arthritis, for which many patients in OCTAVE Induction 1 and 2, and OCTAVE Sustain, reported improvement or no change from baseline with tofacitinib treatment. Clinicaltrials.gov:NCT01465763 ; NCT01458951; NCT01458574